An Analytical Approach in Calculation of the inductance of Single-Phase Asynchronous Motors. - Rusdy Hartungi; Luis Gomez- Agustina; Zhihui Ye (Department of Electrical Engineering, Institut Teknologi Nasional Malang, Indonesia, 2021)
In optimizing design of the iron core, it is essential to know the magnetic field of the coil outside the core to get the leakage inductance, because the leakage inductance in this area usually provides high contribution to the flux density in the iron core. In this paper, an analytical solution as an alternative to three-dimensional FEM (finite element method) to calculate the field outside the iron core by solving analytical equation using MathCAD is presented. The analytical method provides results that are close to result given by three-dimensional FEM, but with the great advantage of dramatically reduced computing time.